Control of the transmission length in the prestressed hollow-core slabs using values of the strand end slip - Victor Tur; Stanisław Fic (Budownictwo i Architektura, 2013)
It is shown [1] that even though the production of precast pre-tensioned concrete elements started more than 50 years ago, no one has ever succeeded in determining the real transmission length or in obtaining adequate measures to control it, due to the quality of the production. These arrears are confirmed by the study of existing standards.